Bias in the eye of beholder? 25 years of election monitoring in Europe. Issue 5 (4th July 2022) - Mochtak, Michal; Drnovsky, Adam; Lesschaeve, Christophe
ABSTRACT: Building on the original corpus of OSCE monitoring reports, the article analyses quarter of century of election monitoring in Europe and assesses the congruence of OSCE written assessments with expert views. We show that, overall, the OSCE monitoring reports are highly correlated and congruent with expert assessments. More importantly, the level of congruence between the two increases with time. However, we also identify various forms of biases rooted in strategic interests and institutional preconditions. Mainly, we show that OSCE has a strong and positive bias towards Russia and its allies when it comes to election assessments indicating defensive and lenient stances. We theorize this mechanism as a pushback effect and show that although Russia's effort to cripple the activities of OSCE in the past two decades was not successful, OSCE was effectively forced into a defensive position producing less critical assessments than reality warrants.